Corporate social responsibility as a driver of competitiveness: A systematic literature review (2020-2024) - Ñiquen-Levy, Randolf; Loayza-Mendocilla, Eleany; Caceres-Oyarce, Mercedes (LACCEI, 2025)
THIS RESEARCH AIMED TO SYNTHESIZE FINDINGS ON CORPORATE SOCIAL RESPONSIBILITY (CSR) AND ITS RELATIONSHIP WITH BUSINESS COMPETITIVENESS IN PERU BETWEEN 2020 AND 2024, IDENTIFYING TRENDS AND GAPS TO GUIDE FUTURE RESEARCH. THE PRISMA METHODOLOGY WAS EMPLOYED, CULMINATING IN THE SELECTION OF 25 RELEVANT ARTICLES, WITH 60% SOURCED FROM SCOPUS AND 40% FROM WOS. THE "JOURNAL OF COMPETITIVENESS" EMERGED AS THE MOST FREQUENTLY REFERENCED PUBLICATION (12%), FOLLOWED BY THE "REVISTA VENEZOLANA DE GERENCIA" AND THE "JOURNAL OF CLEANER PRODUCTION" (8% EACH). SPAIN LED THE COUNTRY RANKINGS WITH 12% OF STUDIES, WHILE 2020 WAS THE MOST PROLIFIC YEAR (27.98%), FOLLOWED BY 2023 (24.02%). A BIAS RISK ASSESSMENT REVEALED THAT 70% OF THE STUDIES EXHIBITED LOW RISK, 20% UNCERTAIN RISK, AND 10% CRITICAL RISK.THE FINDINGS DEMONSTRATE THAT CSR SIGNIFICANTLY ENHANCES COMPETITIVENESS BY INFLUENCING ORGANIZATIONAL PERFORMANCE FACTORS SUCH AS REPUTATION, BRAND IMAGE, AND CUSTOMER LOYALTY. IN ECUADOR'S MANUFACTURING SECTOR, CSR AND GREEN INNOVATION DRIVE COMPETITIVENESS BY FOSTERING EMPLOYEE WELL-BEING AND LEVERAGING FORMAL CSR TOOLS FOR DIFFERENTIATION. SIMILARLY, IN SPAIN'S AGRICULTURAL SECTOR, THE INTEGRATION OF CSR WITH SUSTAINABLE TECHNOLOGICAL INNOVATION HAS PROVEN TO BOOST BOTH COMPETITIVENESS AND SUSTAINABILITY. THESE RESULTS UNDERSCORE THE PIVOTAL ROLE OF CSR IN SHAPING SUSTAINABLE BUSINESS STRATEGIES AND SECURING COMPETITIVE ADVANTAGES IN DYNAMIC MARKETS.